The relationship between digital technostress and cyber moral disengagement among college students: a moderated mediation model of psychological resilience, self-efficacy, and online self-control - Hu, Ruyan; Gao, Qian; Hu, Rufei; Liu, Guofeng; Zhang, Liyuan (Frontiers in Psychology, 2025)
This study explores the relationship between digital technostress and cyber moral disengagement among college students, with a particular focus on the mediating role of psychological resilience, self-efficacy, and the moderating role of online self-control. This study conducted a questionnaire survey on 1980 college students using the Digital Technostress Scale, Cyber Moral Disengagement Questionnaire, Internet Usage Self- Control Scale, Psychological Resilience Scale, and Self-efficacy Scale. The results indicate that: (1) There is a significant positive correlation between digital technostress and cyber moral disengagement; (2) The independent and chain mediated pathways of psychological resilience and self-efficacy between digital technostress and cyber moral disengagement are established; (3) The online self-control plays a moderating role in the relationship between digital technostress and cyber moral disengagement. In summary, this study highlights the mediating role of psychological resilience and self-efficacy, as well as the moderating role of online self-control. This study advances theoretical understanding of the mechanisms linking digital technostress and cyber moral disengagement, and underscores the pivotal role of online self-control in mitigating cyber moral disengagement among college students.